REDUCTION OF INTRAMEDULLARY APOPTOSIS AFTER STEM CELL TRANSPLANTATION IN BLACK AFRICAN VARIANT OF PEDIATRIC SICKLE CELL ANEMIA. - Antonella Isgrò; Pietro Sodani; Marco Marziali; Javid Gaziev; Daniela Fraboni; Katia Paciaroni; Cristiano Gallucci; Gioia De Angelis; Cecilia Alfieri; Michela Ribersani; Daniele Armiento; Andrea Roveda; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Purpose: Allogeneic hematopoietic stem cell transplantation (HSCT) is the only curative treatment for sickle cell anemia (SCA). We report our experience with transplantation in children with the Black African variant of SCA and the effects of transplant on erythroid compartment in bone marrow (BM). Patients and Methods: Twenty-seven consecutive patients who underwent BM transplantation from HLA-identical donors following a myeloablative conditioning regimen were included. Using both CD71 and FSC parameters, we obtained three erythroid populations: EryA–C. Ery A (CD71high FSChigh) are basophilic; Ery B (CD71high FSClow) are late basophilic and polychromatic; and Ery C (CD71low FSClow) are orthochromatic erythroblasts and reticulocytes. To analyze the effect of transplantation on intramedullary apoptosis, we studied Fas (CD95+) and caspase-3 expression in erythroblast subpopulations. Results: All patients experienced sustained engraftment, and all surviving patients remained free of SCA-related events after transplantation. The erythroid population showed expansion in the BM at baseline. After transplant, levels decreased, especially of Ery C, in parallel to reduced Fas expression and an initial caspase 3 increase in erythroid population, similar to reported later steps of “normal” erythroid maturation. Conclusions: The results suggest a good chance of cure for children with SCA, with an excellent survival rate. We also observed “normalization” of erythroid populations in parallel with a decreased intramedullary apoptosis rate, suggesting normal erythroid maturation in ex-SCA patients after HSCT.